Detection of BVDV - Comparative Evaluation of RT-qPCR, PCR and RT-LAMP - Wei, Suocheng (Acta Scientiae Veterinariae, 2024)
Background: Bovine viral diarrhea virus (BVDV) causes various diarrhea symptoms in cattle, which leads to the mortality increase of infected animals. Therefore, this disease causes significant economic losses of cattle industry over the world. Recent advances in molecular diagnosis methods based on PCR technique allow rapid detection of BVDV in the clinical sample. However, each method has its weaknesses in the specificity and sensitivity. Therefore, it is highly necessary to develop a more specific and precise detection method. Loop-mediated isothermal amplification (LAMP) offers an alternative DNA amplification method, which amplifies DNA with high specificity, efficiency and rapidity. Compared with the PCR-based assays, LAMP is more resistant to PCR inhibitors and can be carried out in a shorter reaction time. The present study aimed to select an accurate, quick and cost-effective detection assay of bovine viral diarrhea virus (BVDV). Materials, Methods & Results: Specific primers were designed and synthesized using Primer Premier 5.0 based on NADL strain of BVDV and BVDV1/JL. The conventional PCR was established according to TaKaRa Ex Taq reagent manual and the reaction systems and reaction conditions were optimized for improving reaction specificity and amplification efficiency. RT-qPCR was constructed using according to the TB Green Premium Ex Taq reagent instruction. Five gradients of primer concentrations (6 μM, 8 μM, 10 μM, 12 μM, 14 μM and 16 μM) were set to select an optimum concentration. The appropriate annealing temperature was determined based on 8 gradients temperatures from 53°C to 61°C within 20 s - 80 s. The kinetics curve, standard curve and melting curve of RT-PCR amplification were drawn based on the recombinant plasmids of 8.134 × 108 - 8.134 × 104 copies/μL. The specificity between 3 methods was evaluated on the bases of simultaneous detection of 6 viruses including BVDV, BPV, BPIV, BCoV, BRV and CSFV. Both sensitivity and repeatability of 3 assays were also compared according to determining different concentrations of plasmid standards from 8.134 × 1010 to 8.134 × 100 copies/μL and by testing plasmid standards in triplicate. The coefficient of variation of the intra-assay and inter-assay were calculated. Kappa consistency testing and pairing χ2 test were performed to assess their clinical practicality. Three developed methods of PCR, RT-qPCR and RT-LAMP could only detect BVDV, indicating that the developed methods had excellent specificity. Eleven gradients of plasmid standards from 8.134 × 1010 to 8.134 × 100 copies/ μL were tested with these detection assays. Minimum detection limits were 8.134 × 104, 8.134 × 101 and 8.134 × 102 copies/ μL for PCR, RT-qPCR, and RT-LAMP, respectively. The RT-qPCR method has the highest sensitivity, which was 10-folds and 1,000-folds higher than RT-LAMP and PCR. In conclusion, the constructed PCR, RT-qPCR and RT-LAMP assays had excellent specificity, sensitivity and reproducibility. The sensitivity of RT-qPCR was 10-folds and 1,000-folds higher than RT-LAMP and PCR. Discussion: In the present study, the conventional PCR, RT-qPCR and RT-LAMP methods were established and optimized based on the specific primers of BVDV NADL strain. The results indicated the developed PCR had excellent specificity. Meanwhile, the comparisons between PCR, RT-qPCR and RT-LAMP assays indicated that these methods had excellent specificity only for BVDV. The minimum detection limits for PCR, RT-qPCR and RT-LAMP were 8.134 × 104, 8.134 × 101 and 8.134 × 102 copies/ìL, respectively. RT-qPCR sensitivity was 10-folds and 1,000-folds higher than that of RT LAMP and PCR. Kappa and McNemar calibration verified and supported these results. Our findings provided the technical support for early screening and preventing of BVDV. Keywords: Bovine viral diarrhea virus, RT-LAMP, RT-qPCR.